Behavioural development of school-aged children who live around a multi-metal sulphide mine in Guangdong province, China: a cross-sectional study - Deng Xue-Qing; Chen Wei-Qing; Ling Wenhua; Wang Mao; Song Hong; Lu Ci-Yong; Bao Qing-Song; Hao Yuan-Tao; Rao Shaoqi (BMC, 2009)
Abstract Background The deleterious biological effects of low-level, long-term exposure to heavy metals are well known, and children are the most susceptible population. Dabaoshan Mine in the southeast of Guangdong Province is at high risk of discharging multi-metals pollutants into a local river (Hengshihe) and the surrounding area. The present study aimed to estimate relationships between measured multi-metal exposures and the presence of behavioural problems for the school-aged children in the polluted area. Methods A cross-sectional study was performed. Children aged 7-16 years living in three villages of the Hengshihe area with different degrees of heavy-metal pollution participated in this study. Local environmental samples (water and crops) and children's hair were collected, and concentrations of heavy metals were determined. The Child Behaviour Check-list (CBCL) was used to assess the presence of behaviour problems. General linear regression was used to analyze the contribution of hair metals to each CBCL subscale with adjustment for socio-demographic confounding factors. Results Multiple regression analyses revealed significant effects of hair lead, cadmium and zinc levels on CBCL subscales. Log-transformed hair lead, cadmium and zinc levels accounted for an incremental of 8% to 15% variance in anxious/depressed, withdrawn, somatic complaints, social problems, thought problems, attention problems, delinquent behaviour and aggressive behaviour. The concurrent log-transformed hair lead and zinc levels were strongly associated with all subscales while the concurrent log-transformed hair cadmium was only significantly associated with withdrawn, social problems and attention problems. Conclusion This study reveals that heavy metal exposure was associated with increased risk of behavioral problems for school-aged children.